Mapping the immunological landscape and emerging immunotherapeutic strategies in cervical cancer: a comprehensive review - Xinyi Zhang; Wenyang Nie; Wenwen Shao; Qian Guo (Frontiers in Oncology, 2025)
Cervical cancer continues to pose a considerable global health challenge, especially in low- and middle-income nations, although progress in screening and vaccine efforts. In recent years, immunotherapy has emerged as a promising treatment option; nevertheless, its efficacy in cervical cancer is constrained by the intricate and heterogeneous tumor immune microenvironment. Reliable biomarkers to predict which patients will benefit from immunotherapy are lacking. The heterogeneity of the immune landscape across patients adds further complexity. This paper offers a thorough examination of the immunological landscape in cervical cancer, highlighting the interactions among tumor cells, immune infiltrates, and stromal elements. Moreover, we investigate how advanced technologies—such as single-cell RNA sequencing, spatial transcriptomics, and multiplex imaging—are transforming our comprehension of immunological heterogeneity and uncovering new therapeutic targets. We seek to delineate present problems and potential pathways in the development of effective, tailored immunotherapies for cervical cancer by integrating genetic analysis with immunological insights.